ANALISIS KEPUASAN PELANGGAN ATAS KUALITAS PELAYANAN PADA PT AUTOMOBIL JAYA MANDIRI WULING DI SURAKARTA - Endah Astuti; Eny Kustiyah; Sri Hartono (JURNAL ILMIAH EDUNOMIKA, 2019)
The purpose of this study was to determine the effect of service quality on customer satisfaction PT. Automobil Jaya Mandiri Wuling Surakarta partially and simultaneously. Primary data sources were obtained from questionnaires distributed to consumers with a sample of 95 people, while secondary data were obtained from PT. Automboil Jaya Mandiri Wuling Surakarta. The analytical tool used is quantitative descriptive analysis. Based on the results of the t test, it can be concluded that there is a partial effect between tangible and assurance on customer satisfaction at PT. Automobil Jaya Mandiri Wuling Surakarta. F test results show that there is a simultaneous influence between tangible, reliable, responsible, assurance, empathyvvariables on customer satisfaction at PT. Automobil Jaya Mandiri Wuling Surakarta. The results of multiple linear regression tests obtained by the equation Y = 1,219 + 0.763 X1 - 0.064 X2 + 0.130 X3 + 0.748 X4 - 8.644X5 €. From the regression equation it can be seen that the most dominant variable influencing consumer satisfaction is the physical evidence variable with a coefficient of 0.763. R2 (R Square) test obtained a result of 0.609 or 60.9% which means that customer satisfaction with the Dealer of PT. Automobil Jaya Mandiri Wuling Surakarta is influenced by variable tangiable, reliable, responsible, assurance, empathy of 60.9%. And other factors that influence customer satisfaction at PT. Automobil Jaya Mandiri Wuling Surakarta. of 0.391 (39.1%) expected by PT. Automobil Jaya Mandiri Wuling Surakarta needs to implement and develop aspects of service to consumer satisfaction which include tangible (physical evidence), reliability (reliability), responsiveness (responsiveness), assurance (empathy), empathy (empathy), so as to obtain a more market share well. Keywords: Service Quality, Tangible, Reliability, Responsiveness, Assurance, Empathy, and Customer Satisfaction